2003
DOI: 10.1128/aem.69.9.5089-5095.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Inducible Chlorophenol O -Methyltransferase from Trichoderma longibrachiatum Involved in the Formation of Chloroanisoles and Determination of Its Role in Cork Taint of Wines

Abstract: A novel S-adenosyl-L-methionine (SAM)-dependent methyltransferase catalyzing the O methylation of several chlorophenols and other halogenated phenols was purified 220-fold to apparent homogeneity from mycelia of Trichoderma longibrachiatum CECT 20431. The enzyme could be identified in partially purified protein preparations by direct photolabeling with [methyl-3 H]SAM, and this reaction was prevented by previous incubation with S-adenosylhomocysteine. Gel filtration indicated that the M r was 112,000, and sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Methylating reactions have been confirmed with a partially purified chlorophenol O-methyltransferase from Trichoderma longibrachiatum isolated from cork (3,13). In addition, the participation of bacteria, mainly Streptomyces spp.…”
mentioning
confidence: 78%
“…Methylating reactions have been confirmed with a partially purified chlorophenol O-methyltransferase from Trichoderma longibrachiatum isolated from cork (3,13). In addition, the participation of bacteria, mainly Streptomyces spp.…”
mentioning
confidence: 78%
“…In addition, most research works have preferred S-adenosyl-L-methionine (SAM), which was produced from methionine (Met), to be the intermediary to induce the reaction of xenobiotic methylation through the Met cycle (Finkelstein, 1990;Reed et al, 2004). Recent studies showed that some halogenated phenols also could induce the SAM-dependent methyltransferase to catalyze o-methylation (Neilson et al, 1988;AlvarezRodriguez et al, 2002;Coque et al, 2003). Accordingly, in this work, it can be proposed that during the TBP methylation, the methyl originating from the formic acid was transferred to the xenobiotic substrate TBP via the Met cycle, and the reactions including the o-methylation and the debromination co-occurred during the xenobiotic metabolism (Neilson et al, 1988;Harper et al, 1989;AlvarezRodriguez et al, 2002;Coque et al, 2003).…”
Section: Mechanisms Of Tbp Metabolismmentioning
confidence: 99%
“…Methyltransferases requiring divalent cations for optimal activity are known (33)(34)(35)(36)(37)(38), and we next evaluated the activity of NcsB1 in the presence of different metal ions. Notably, the presence of EDTA resulted in a 2-fold higher activity; inclusion of Mn 2ϩ and Ca 2ϩ in the reactions resulted in a slightly higher activity, whereas inclusion of Mg 2ϩ afforded a slight decrease in enzyme activity.…”
Section: Opitimization Of Ncsb1-catalyzed O-methylation In Vitro-mentioning
confidence: 99%